2018
DOI: 10.1261/rna.067413.118
|View full text |Cite
|
Sign up to set email alerts
|

Hnrnpab regulates neural cell motility through transcription of Eps8

Abstract: Cell migration requires a complicated network of structural and regulatory proteins. Changes in cellular motility can impact migration as a result of cell-type or developmental stage regulated expression of critical motility genes. Hnrnpab is a conserved RNA-binding protein found as two isoforms produced by alternative splicing. Its expression is enriched in the subventricular zone (SVZ) and the rostral migratory stream within the brain, suggesting possible support of the migration of neural progenitor cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…For probands with HNRNPAB variants, DD/ID is common, as are delayed speech and language, ASD, hypotonia, and strabismus. Little is known about hnRNPAB outside of cancer, but it has been shown to regulate expression of neurodevelopmental genes and those involved in glutamate signaling, as well as neural cell motility [ 133 , 134 ]. Probands with HNRNPH3 -related disorder have a high prevalence of DD/ID, like the other HNRNPH disorders, although they manifest characteristic hearing loss as well.…”
Section: Discussionmentioning
confidence: 99%
“…For probands with HNRNPAB variants, DD/ID is common, as are delayed speech and language, ASD, hypotonia, and strabismus. Little is known about hnRNPAB outside of cancer, but it has been shown to regulate expression of neurodevelopmental genes and those involved in glutamate signaling, as well as neural cell motility [ 133 , 134 ]. Probands with HNRNPH3 -related disorder have a high prevalence of DD/ID, like the other HNRNPH disorders, although they manifest characteristic hearing loss as well.…”
Section: Discussionmentioning
confidence: 99%
“…Romer-Seibert et al [152] Hnrnpab Eps8 SVZ cell migration Lampasona et al [156] NSC neural stem cell, OB olfactory bulb cortical development [65]. As a second example, timed Wnt3 secretion from thalamocortical axons around midneurogenesis regulates both the composition of ribosomal proteins and the subset of mRNAs that are associated with polysomes [34].…”
Section: Rabgef2mentioning
confidence: 99%
“…Sinnamon et al (6) have reported that hnRNP AB may serve a key role in the maintenance, differentiation and survival of neuronal stem cells by activating glutamate signalling pathways. Lampason et al (7) demonstrated that hnRNP AB promoted the migration of normal neural cells by regulating exocrine gland-secreted peptide 8 transcription during the development of the central nervous system in mouse models. Other studies have revealed that abnormal hnRNP expression serves an important role in the occurrence and development of malignant tumours, including lung cancer (8), hepatocellular carcinoma (9) and CRC (10).…”
Section: Introductionmentioning
confidence: 99%